Considering Comparison: A Method for Religious Studies, by Oliver Freiberger - Appleton, Naomi (Religions of South Asia, 2021)
Considering Comparison: A Method for Religious Studies, by Oliver Freiberger. New York: Oxford University Press, 2019. 256 pp., £64 (hb). ISBN 978-0-19996-500-7.